Five years after Carmody: practitioners' views of changes, challenges and research in child protection. (21st June 2019) - Zuchowski, Ines
Abstract: Child protection work is a complex and difficult area of practice, one that is closely scrutinised and criticised, and impacts on the lives of many children. In Australia, child protection systems are overloaded, and increasing numbers of children and families receive child protection interventions each year. This study explored the views of North Queensland practitioners who work in the child protection field, examining changes and challenges in this field of practice, and their suggestions for the future research that is needed in child protection. The study took place 5 years after the 2013 Queensland Carmody inquiry into child protection intervention, which recommended sweeping changes to the child protection system. Twenty-two practitioners participated in this study. Respondents reported an increase in the complexity of cases, a gap in legislation change/practice frameworks and practice, and the application of trauma-informed practice. They highlighted the intersection of child protection, domestic violence and family law and observed that women and children continue to be exposed to violence because of Family Law Court orders. Respondents identified a number of areas where research is needed.